THE IMPACT FACTORS OF CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE - Maidani Maidani; Murti Wijayanti; Rakhmat Purnomo (Faculty of Economics and Business, University of Pasundan, 2020)
This research study purpose is to analyze the impact of profitability, independent members of commissioner board, leverage and public shareholders on Corporate Social Responsibility (CSR) Disclosure by using 27 companies listed on Indonesia stock exchange and publishing Sustainability Report for the year during 2015 – 2017 as a sample. Using multiple linear regression as data analysis method, the results show that the proportion of independent board of commissioner of their existence can be a counterweight to various parties so as to encourage companies to disclose CSR, while the higher leverage level, the more likely the company will violate the credit agreement so that the company will seek to report higher earnings now. Therefore, in order for reported earnings to be high, the manager reduces costs, including the costs of disclosure of social responsibility. While profitability, and public share ownership have no effect on CSR Disclosure.